Bridging the credit gap for sustainable medicinal plant value chain development in Northwestern Vietnam. Issue 4 (5th August 2019) - Luan, Do Xuan
Abstract : Purpose: The purpose of this paper is to explore the existence and determinants of the credit gap in the cinnamon value chain development in Northwestern Vietnam. Design/methodology/approach: A multi-stage sampling of 548 cinnamon households and a Heckman Selection Model were applied to examine their credit access constraints. In-depth interviews with cooperatives, enterprises, banks and relevant government agencies were further conducted to explain the credit gap. Findings: In the total 52.74 percent of households that received credit, 24.56 percent of them received an insufficient amount of credit as registered. In addition, 35.77 percent of total households are credit rationed. Although all enterprises and cooperatives had been successful in applying for credit as long as they have collateral, none of them received the full credit amount requested. The credit amount received satisfied 80.64, 43.03 and 44.28 percent of the demand by households, cooperatives and enterprises, respectively. The lack of valuable collateral assets is the most important factor explaining this credit gap. Moreover, membership in a farmer-based union or ownership of a bank account increases the probability of access to credit. Educated household heads with a larger farm size and the Kinh ethnic majority are positively associated with a larger amount of credit. Households with conventional cinnamon farming, more dependents and union non-membership are more likely to be credit rationed. Practical implications: A reform on collateral management, facilitating access to bank accounts, capacity building for local farmer-based unions, organic certification, granting land use rights and facilitating a platform to share reliable information between relevant actors are needed to bridge the credit gap. Originality/value: This paper analyses the determinants of credit access constraints by key actors in a medicinal plant value chain that was insufficiently discussed by previous studies in the field.